Reliable H∞ filtering for the SP resonant ICPT system with stochastic multiple sensor faults. (November 2021) - Zhu, Shuangxin; Tian, Engang; Liu, Jinliang; Chen, Hongtian
Abstract: The inductively coupled power transfer (ICPT) system is one of the most important system in the wireless power transfer field. In this paper, the reliable H ∞ filtering problem is considered for the ICPT system based on the series–parallel (SP) resonant compensation network. A more general SP resonant ICPT system model is proposed with considering external disturbances and multiple sensor faults. The sensor faults are assumed to happen in a random way, which are described by a set of stochastic variables satisfying certain statistical features. The main purpose of the addressed problem is to design an H ∞ filtering scheme such that the filtering error dynamics are asymptotically mean-square stability (AMSS). For this purpose, a generalized state-space averaging (GSSA) model is built to characterize dynamical behaviors of the SP resonant ICPT system first. Then the filtering-error system with stochastic sensor faults is established via the GSSA model. By virtue of an extended Lyapunov function, a sufficient condition is given to achieve the AMSS of the system and H ∞ performance requirement. Subsequently, the H ∞ filtering gains are obtained by solving a set of linear matrix inequalities. Finally, a simulation example is provided to verify the availability and reliability of the proposed filtering scheme.